Development of Learning Media Through Bookwidgets for A1 Vocabulary - Amanda Putri Ayu Gayatri; Hafniati, Hafniati (Asian Journal of Applied Education (AJAE), 2024)
The purpose of this study is to create learning media with the help of Bookwidgets for A1 level vocabulary. This research is a development research, the method used in this study is qualitative descriptive and uses Richey and Klein's theory, which consists of three phases, namely: 1) planning, 2) production, 3) evaluation. The data of this research was obtained from the vocabulary on the theme, Guten Appetit" in the book Netzwerk neu A1 Kursbuch from pages 44 to 54. The vocabulary cited on the theme is nouns, verbs, and adjectives. This research was conducted at the Foreign Language Laboratory, Faculty of Languages and Arts, State University of Medan. The learning media was created with the help of the Bookwidgets web platform. The result of the creation of the media is a learning medium for learning Germany vocabulary, which consists of learning materials and exercises. Learning materials and media are validated by experts, namely material experts and media experts. The validation results on learning materials and media were 95. With this, it can be said that learning materials and media are good and suitable to be used as vocabulary learning media.